Using leaf spectroscopy and pigment estimation to monitor indoor grown lettuce dynamic response to spectral light intensity - Cammarisano, Laura; Graefe, Jan; Körner, Oliver (Frontiers in Plant Science, 2022)
Rising urban food demand is being addressed by plant factories, which aim at producing quality food in closed environment with optimised use of resources. The efficiency of these new plant production systems could be further increased by automated control of plant health and nutritious composition during cultivation, allowing for increased produce value and closer match between plant needs and treatment application with potential energy savings. We hypothesize that certain leaf pigments, including chlorophylls, carotenoids and anthocyanins, may be good indicator of plant performance and related healthy compounds composition and, that the combination of leaf spectroscopy and mathematical modelling will allow monitoring of plant cultivation through noninvasive estimation of leaf pigments. Plants of two lettuce cultivars (a green- and a red-leaf) were cultivated in hydroponic conditions for a period of 18 days under white light spectrum in climate controlled growth chamber. After that period, plant responses to white light spectrum (‘W’) with differing blue wavelengths (‘B’, 420 - 450 nm) percentage (15% ‘B15’, and 40% ‘B40’) were investigated for a 14 days period. The two light spectral treatments were applied at photon flux densities (PFDs) of 160 and 240 µmol m-2 s-1, resulting in a total of four light treatments (160WB15, 160WB40, 240WB15, 240WB40). Chlorophyll a fluorescence measurements and assessment of foliar pigments, through destructive (in vitro) and non-destructive (in vivo) spectrophotometry, were performed at 1, 7 and 14 days after treatment initiation. Increase in measured and estimated pigments in response to WB40 and decrease in chlorophyll:carotenoid ratio in response to higher PFD were found in both cultivars. Cultivar specific behavior in terms of specific pigment content stimulation in response to time was observed. Content ranges of modelled and measured pigments were comparable, though the correlation between both needs to be improved. In conclusion, leaf spectroscopy combined with mathematical modelling may represent a potential noninvasive and real-time technique to monitor, and control, plant growth and nutritious quality in controlled environment agriculture.